Legal Protection of Works Produced by Artificial Intelegence - Al Idrus, Rizki; Akyuwen, Rory Jeff; Labetubun, Muchtar Anshary Hamid (TATOHI: Jurnal Ilmu Hukum, 2025)
Introduction: The development of Artificial Intelligence-based technology in the digital era has implications for human life, one of which is law. One of the interesting legal issues to study related to artificial intelligence is copyright protection.Purposes of the Research: This study aims to determine whether creations resulting from artificial intelligence can be classified as intellectual property and to determine whether artificial intelligence can be equated with employees who work based on employment relationships (Works Made for Hire).Methods of the Research: The research method used by the author is normative. The legal materials used by the author are primary legal materials that are authoritative in the form of laws and regulations, secondary legal materials, namely legal materials that support primary legal materials, namely literature studies (journals and books), and Tertiary (mass media, legal dictionaries, journals, and the internet). The materials obtained were then analyzed using a qualitative descriptive method, namely by analyzing legal materials and then systematically arranged to obtain conclusions.Findings of the Research: The results of the study are 1) showing that the creations produced by AI do not meet the subjective concept of a creation, but meet the objective concept of a creation which therefore could possibly obtain copyright protection. 2) The Works Made For Hire doctrine can be used as a solution, the AI system will be considered an employee. The creation will be allocated directly to the user or programmer, because the AI system is a tool that helps the creator in producing a creation.